ALK-positive histiocytosis with KIF5B-ALK fusion in the central nervous system - Lucas, Calixto-Hope G.; Gilani, Ahmed; Solomon, David A.; Liang, Xiayuan; Maher, Ossama M.; Chamyan, Gabriel; Kleinschmidt-Demasters, Bette K.; Perry, Arie (Journal of Economic Literature, 2019)
Histiocytic disorders are uncommon and often affect multiple organ systems. They pose diagnostic challenges because of their rarity and the fact that the nosology of these lesions is still being decided. ALK-positive histiocytosis is one of the newest subtypes and was originally described about 10 years ago, wherein there was a predilection for neonates and infants with multi-organ involvement [1]. Since then, ten additional cases have been reported, with only one having exclusive intracranial disease, along with involvement of the cavernous sinus [2, 3]. Here, we report two additional cases with exclusive involvement of the central nervous system. Case 1 is a 7-year-old girl who presented with a 1-month history of headaches and vomiting. Magnetic resonance imaging (MRI) showed an infiltrating 3 cm mass in the cerebellar vermis. The mass was associated with diffusion restriction and was radiologically suspicious for medulloblastoma (Fig. 1a). She underwent gross total resection followed by observation with MRI every 3 months. Postoperative whole-body PET–CT scan showed no evidence of systemic disease. At 1-year postoperative follow-up, there is no evidence of recurrence on neuroimaging. Her only neurologic deficit is a minimal slurring of speech and difficulty with phonation. Case 2 is a 10-year-old girl who presented with medically refractory seizures and was found to have a homogenously enhancing 1.4 cm mass in the right pericentral cortical region on head MRI (Fig. 1g). She underwent focal corticectomy followed by observation. Postoperatively, she has been doing well and has only had one reported seizure. She has not had a recurrent seizure while on antiepileptic therapy. At 6-month postoperative follow-up, there is no evidence of recurrence on neuroimaging. She has no remarkable findings on physical and neurological exam. Consistent with prior reported cases, microscopic examination in both cases showed sheet-like aggregates of large epithelioid cells with irregularly folded nuclei and fine chromatin, foamy cells, Touton-like giant cells, and focal emperipolesis (Fig. 1b–e, h). Immunohistochemical workup in both cases showed ALK expression (Fig. 1f, i), Factor XIIIa, CD68 (Fig. 1j), and CD163 (Fig. 1k) positivity, patchy staining for S-100 protein, and lack of CD1a, BRAF V600E, or GFAP reactivity, although the latter highlighted adjacent and entrapped brain parenchyma with reactive astrocytosis (Fig. 1l). The histopathology observed in these cases of ALK-positive histiocytosis show overlapping features with those of Erdheim–Chester disease (ECD), juvenile xanthogranuloma (JXG), Rosai–Dorfman disease (RDD), and Langerhans cell histiocytosis (LCH). In particular, foamy cells, Touton-like giant cells, variable S-100 staining, and the presence of Factor XIIIa expression suggests the possibility of JXG or ECD [4]. Emperipolesis can be seen in RDD and folded or grooved nuclei are present in LCH. A CD1a immunostain can be used to further rule out LCH. Rarely, ALK-positive histiocytosis can also be confused with astrocytic lesions, particularly at intraoperative consultation Electronic supplementary material The online version of this article (https ://doi.org/10.1007/s0040 1-019-02027 -7) contains supplementary material, which is available to authorized users.